2011
DOI: 10.1186/1476-511x-10-154
|View full text |Cite
|
Sign up to set email alerts
|

Enchanced levels of apolipoprotein M during HBV infection feedback suppresses HBV replication

Abstract: BackgroundChronic liver diseases can interfere with hepatic metabolism of lipoproteins, apolipoproteins. Hepatitis B virus (HBV) is a major etiological agent causing acute and chronic liver diseases. Apolipoprotein M (ApoM) is a high-density lipoprotein (HDL) apolipoprotein and exclusively expressed in the liver parenchyma cells and in the tubular cells of the kidney. This study was to determine the correlation between HBV infection and ApoM expression.Materials and methodsSerum ApoM levels in patients with HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
2
15
1
Order By: Relevance
“…Previous studies showed that HBV enhances apoM mRNA and protein expression, and that elevated levels of apoM suppress HBV protein expression and viral replication in HepG2 cells. However, these studies found no correlation between HBV viral load and apoM levels in patients with CHB [13]. Conversely, in this study, we found that higher HBV DNA levels were associated with higher serum apoM concentrations in patients with HBeAg-negative, but not HBeAg-positive, CHB.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Previous studies showed that HBV enhances apoM mRNA and protein expression, and that elevated levels of apoM suppress HBV protein expression and viral replication in HepG2 cells. However, these studies found no correlation between HBV viral load and apoM levels in patients with CHB [13]. Conversely, in this study, we found that higher HBV DNA levels were associated with higher serum apoM concentrations in patients with HBeAg-negative, but not HBeAg-positive, CHB.…”
Section: Discussioncontrasting
confidence: 88%
“…Similarly, HepG2 cells transfected with an infectious HBV clone were found to express significantly higher levels of apoM mRNA and protein than uninfected HepG2 cells in vitro. Moreover, apoM suppressed HBV replication in HepG2 cells [13]. However, the association between apoM expression and HBV replication rate in CHB patients is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, serum high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol (TC) and apolipoprotein B (ApoB) levels are decreased in hepatitis C virus-infected patients [ 15 17 ]. Our previous studies also found that HBV inhibited the synthesis and secretion of ApoB by inhibiting microsomal triglyceride transfer protein (MTP) expression [ 18 ], and the levels of serum ApoM was significantly elevated in patients as compared to healthy individuals, and enhanced ApoM levels in HBV infection may in turn suppress HBV replication [ 19 ]. Moreover, both Wang et al and Jiang et al confirmed that HBV inhibited the synthesis and secretion of ApoA1 in vivo and in vitro [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The APOM in serum of severe patients was downregulated compared with healthy and non-severe COVID-19 patients. Regulation of serum APOM has also been observed in hepatitis B virus (HBV) patients (Gu et al, 2011).…”
Section: Dysregulated Macrophage and Lipid Metabolismmentioning
confidence: 99%